ANALYSIS OF BUDGET DEFICIT AND ITS IMPLICATION ECONOMIC GROWTH REGENCY / CITY IN THE PROVINCE OF WEST KALIMANTAN - B2051131006, VIKTOR (Jurnal Ekonomi Daerah (JEDA), 2016)
The study entitled "Analysis of Budget Deficit and Its Implication Economic Growth Regency / City in the province of West Kalimantan," aims to determine the effect Indirect Expenditures, direct expenditure and budget deficit of the Economic Growth Regency / City in the province of West Kalimantan. This type of research is descriptive explanatory. The variables analyzed are indirect spending (BTL), direct expenditure (BL), budget deficits, and economic growth (PE), the data obtained from DJPK in the form of panel data in 2009 through 2014 in 14 districts / cities. The analysis tool is a path analysis. The results showed that the indirect spending (BTL) positive and significant impact on the budget deficit, but did not significantly affect economic growth, direct spending a significant negative effect on the budget deficit and significantly affect economic growth, the budget deficit based on research results not significant effect on economic growth. Based on the results of this study concluded that partial indirect expenditure (BTL) has no effect on economic growth (PE) while direct expenditure (BL) effect on PE in the study period from 2009 through 2014 to 14 districts / municipalities in West Kalimantan Province. Keyword : Shopping indirect, direct expenditure, deficit and economic growth